2014
DOI: 10.1016/j.nlm.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone-induced enhancement of memory and synaptic Arc protein in the medial prefrontal cortex

Abstract: Acute administration of the stress hormone corticosterone enhances memory consolidation in a manner that is dependent upon the modulatory effects of the basolateral complex of the amygdala (BLA). Posttraining administration of corticosterone increases expression of the activity-regulated cytoskeletal-associated protein (Arc) in hippocampal synaptic-enriched fractions. Interference with hippocampal Arc expression impairs memory, suggesting that the corticosterone-induced increase in hippocampal Arc plays a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In addition, our study found that the FA value in the thalamus was reduced, and the FA value in the thalamus was negatively correlated with duration of primary insomnia, which indicated that FA in the thalamus is progressively reduced with disease duration. This could point to an involvement of thalamus in the pathologic structure of primary insomnia, which is particularly critical because important constituents of the biologic clock are located in the thalamus (26). Apart from FA measures, we found radial diffusivity measures attributed to reduced WM integrity, which suggests that a loss of myelination (27,28) in the primary patients is causative for the increased radial diffusivity and consecutively for the reduced FA in the WM tracts.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, our study found that the FA value in the thalamus was reduced, and the FA value in the thalamus was negatively correlated with duration of primary insomnia, which indicated that FA in the thalamus is progressively reduced with disease duration. This could point to an involvement of thalamus in the pathologic structure of primary insomnia, which is particularly critical because important constituents of the biologic clock are located in the thalamus (26). Apart from FA measures, we found radial diffusivity measures attributed to reduced WM integrity, which suggests that a loss of myelination (27,28) in the primary patients is causative for the increased radial diffusivity and consecutively for the reduced FA in the WM tracts.…”
Section: Discussionmentioning
confidence: 64%
“…Posttraining b-adrenergic receptor activation in the BLA increases synaptic expression of ARC protein in the medial prefrontal cortex (McReynolds et al, 2014) and the rostral anterior cingulate (Holloway-Erickson et al, 2012), and blockade of ARC protein expression in either area impairs memory consolidation (Holloway and McIntyre, 2011;McReynolds et al, 2014). Blockade of b-adrenergic receptors in the BLA attenuates the memory enhancement produced by post-training administration of corticosterone, but, in contrast to the BLA-mediated reduction in hippocampal ARC expression, such blockade in the BLA increases ARC expression in the prelimbic region of the medial prefrontal cortex (McReynolds et al, 2014). These findings suggest that the BLA is a regulator of ARC expression elsewhere in the brain.…”
Section: B Basolateral Amygdala Influence On Expression Of Plasticitmentioning
confidence: 99%
“…Indeed, in one recent study with human participants, direct electrical stimulation targeting the BLA improved recognition memory for neutral object images despite participants reporting that they could not detect the stimulation (Inman et al, 2018). These experiments built on prior work in rodents demonstrating that the BLA mediated the influence of emotional arousal on memory performance in tasks such as inhibitory avoidance (McIntyre et al, 2002, 2005; McReynolds et al, 2010, 2014b; Holloway-Erickson et al, 2012; Huff et al, 2013). Thus, existing research suggests that activation of the BLA can modulate memory for the better and can be engaged by emotional arousal or by direct intervention.…”
Section: Introductionmentioning
confidence: 99%